2018
DOI: 10.3389/fphys.2018.01593
|View full text |Cite
|
Sign up to set email alerts
|

Increased Abundance of Lactobacillales in the Colon of Beta-Adrenergic Receptor Knock Out Mouse Is Associated With Increased Gut Bacterial Production of Short Chain Fatty Acids and Reduced IL17 Expression in Circulating CD4+ Immune Cells

Abstract: Emerging evidence suggests an associative link between gut dysbiosis, the autonomic nervous system (ANS) and the immune system in pathophysiology of neurogenic hypertension (HTN). However, the close interplay between these three systems presents us with difficulties in deciphering the cause-effect relationship in disease. The present study utilized beta 1 and 2 adrenergic receptor knock out (AdrB1tm1BkkAdrB2tm1Bkk/J KO) mice to isolate the effects of reduced overall sympathetic drive on gut microbiota and syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 69 publications
1
19
0
Order By: Relevance
“…Yang et al made use of a new bone marrow chimera mouse model that lacked the β-adrenergic receptor 1 or 2 and showed a significant shift in the Bacilli class of Firmicutes in the colon, more specifically in the family of Lactobacillaceae. This was in line with the findings that were published by Bartley et al [117] that showed reduced β-adrenergic signaling leads to beneficial shifts in the gut microbiota. However, no significant change was found in the F/B ratio.…”
Section: Neuronal Innervation and Microbiotasupporting
confidence: 93%
See 1 more Smart Citation
“…Yang et al made use of a new bone marrow chimera mouse model that lacked the β-adrenergic receptor 1 or 2 and showed a significant shift in the Bacilli class of Firmicutes in the colon, more specifically in the family of Lactobacillaceae. This was in line with the findings that were published by Bartley et al [117] that showed reduced β-adrenergic signaling leads to beneficial shifts in the gut microbiota. However, no significant change was found in the F/B ratio.…”
Section: Neuronal Innervation and Microbiotasupporting
confidence: 93%
“…An increased F/B ratio has been associated with obesity [115] and IBD [116]. Therefore, currently it is being used as marker for pathological conditions [117]. Yang et al made use of a new bone marrow chimera mouse model that lacked the β-adrenergic receptor 1 or 2 and showed a significant shift in the Bacilli class of Firmicutes in the colon, more specifically in the family of Lactobacillaceae.…”
Section: Neuronal Innervation and Microbiotamentioning
confidence: 99%
“…In fact, butyrate has been shown to attenuate angiotensin II‐induced hypertension in mice, and both, acetate supplementation or a diet rich in fiber, which substantially increases the production of SCFAs such as acetate, prevented the development of hypertension in deoxycorticosterone acetate (DOCA)‐salt . Increased bacterial production of SCFAs is associated with reduced circulating CD4+ immune cells . Bacterial LPS, through toll‐like receptor (TLR)4 activation, contributes to the low‐grade vascular inflammation and, ultimately, the increased blood pressure present in SHR …”
Section: Introductionmentioning
confidence: 99%
“…17 In fact, butyrate attenuates angiotensin II-induced hypertension in mice 19 and SHR, 8 acetate supplementation or a diet rich in fiber, which significantly raises SCFAs production by gut bacteria, such as acetate, prevented the development of hypertension in DOCA-salt mice, 5 and propionate supplementation exhibited antihypertensive effects in angiotensin II-infused mice. 20 Increased bacterial production of SCFAs has been linked to lower numbers of circulating CD4+ immune cells 21 and its antihypertensive effects were Treg-dependent. 8,20 Bacterial LPS, through tolllike receptor (TLR)-4 activation, contributes to high blood pressure and low-grade vascular inflammation in the SHR model.…”
Section: Introductionmentioning
confidence: 99%